2021
DOI: 10.21203/rs.3.rs-139888/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Design and Fabrication of Soft X ray Suppermirrors

Abstract: W/Si, Ir/SiC, and Pt/C supermirrors were designed by block method and fabricated by magnetron sputtering method. The glancing incident angles are 1.0, 1.4 and 1.7 degree. Pt/C supermirrors show better spectral results than W/Si, Ir/SiC. Pt/C supermirrors also have good angular tolerance, which will benefit opt-mechanic alignment. In addition, Pt layer as outmost one can withstand harsh space environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Furthermore, in the current study, benign tumors showed higher expression of talin-1 compared to normal tissues. These findings are in line with previous studies on the OC patients, indicating that talin-1 expression significantly increases in the OC tissues, while its expression is weak or undetectable in benign and normal ovarian tissues (10,11). Furthermore, these data are in agreement with several reports on the other carcinomas, including CRC (31), prostate cancer (32), nasopharyngeal carcinoma (13), HCC (9), and OSCC (12).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, in the current study, benign tumors showed higher expression of talin-1 compared to normal tissues. These findings are in line with previous studies on the OC patients, indicating that talin-1 expression significantly increases in the OC tissues, while its expression is weak or undetectable in benign and normal ovarian tissues (10,11). Furthermore, these data are in agreement with several reports on the other carcinomas, including CRC (31), prostate cancer (32), nasopharyngeal carcinoma (13), HCC (9), and OSCC (12).…”
Section: Discussionsupporting
confidence: 92%
“…Since talin-1 plays an important role in the interaction between integrin, cytoskeleton, and ECM, dysregulation of this protein has been linked to tumor metastasis and invasion (9). Studies conducted on OC have demonstrated that increased expression of the talin-1 protein is associated with the development of disease and progression to metastasis (10,11). Accordingly, silencing the talin-1 gene could inhibit the invasion and migration of OC cells by preventing epithelial-mesenchymal transition (EMT) (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4−8 Previous studies have shown that NiMo-based materials are an ideal alternative to precious metal catalysts and have higher activity in UOR processes than other metal compounds. 9−11 The catalytic performance can be effectively enhanced via an appropriate nanostructure design, 12 interface engineering, 13 or elemental doping, 14,15 such as, prepared Ni/C composites, 16 NiMoS composites, 17 and Ni−Mo−O composites. 18 Unfortunately, the strong interaction between the active site of the reactants and the intermediates still makes the catalytic performance of UOR catalysts unsatisfactory.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In these reactors, a vertical channel geometry structure in cylindrical or annular form is the ultimate choice of the design of the passive system [7]. The main limitation in air-cooled systems lies in the low heat transfer coefficients which limit their effectiveness [8]. In pursuit of the small, largely autonomous nuclear reactors, there is a need to revisit natural convection in vertical channels for purposes of heat transfer enhancement and design optimization.…”
Section: Introductionmentioning
confidence: 99%